Challenges of Elementary School Management Strategies in The Implementation of Deep Learning - Oktafiyana, Fitri; Yuniarti, Yeni (International Conference on Elementary Education, 2025)
Twenty-first-century education demands a paradigm shift from the mere transfer of knowledge toward the cultivation of critical, creative, collaborative, and communicative thinking skills. The deep learning approach is regarded as a relevant framework to address these demands. However, the reality in elementary schools reveals a significant gap between modern learning expectations and managerial readiness, which remains dominated by administrative and bureaucratic practices. This study aims to analyze the challenges of elementary school management strategies in implementing deep learning and to identify potential solutions. A Systematic Literature Review (SLR) with a descriptive approach was employed, consisting of the stages of identification, selection, analysis, and synthesis of 20 national and international articles published between 2018 and 2025. The findings indicate that the primary challenges lie in unclear strategic direction, limited managerial competence, weak communication, and an individualistic school culture. The study concludes that adaptive, evidence-based management strategies supported by collaborative leadership and the active participation of all school members are essential to fostering a reflective and innovative culture that promotes effective and sustainable deep learning.